Answer:
(p^2−6) (1-q(p^2-6))
Step-by-step explanation:
p^2−6−q·(p^2−6)^2
Put parentheses around the P^2-6 at the beginning of the expression
(p^2-6) -q (p^2−6)^2
Factor out (p^2−6)
(p^2−6) (1-q(p^2-6))
I am sorry i dont understand
Number of points Jill scored in the first 4 games = 4 * 4 = 16
number of points Jill scored in the first 4 games = 6 * 9 = 54
total points Jill scored in 10 games 16 + 54 = 70
the average number of points after 10 games = 70 / 10 = 7 points
" the quotient " means divide
(x/3) - 4 <== ur expression